Sensitive Determination of Five Priority Haloacetic Acids by Electromembrane Extraction with Capillary Electrophoresis. Issue 2 (14th January 2015) - Zhang, Xiaoli; Zhang, Haitao; Liu, Yan; Guo, Lin; Ye, Jiannong; Chu, Qingcui
Abstract A method for sensitive determination of five priority haloacetic acids in drinking water has been developed for the first time based on electromembrane extraction (EME) prior to CZE with capacitively coupled contactless conductivity detection (CZE‐C4D). The target analytes were extracted from 10 mL of the sample solution (donor phase), through the supported liquid membrane (using a polypropylene membrane supporting 1‐octanol), and into 10 µL of 50 mmol/L NaAc solution (acceptor phase). The extracted solution was directly analyzed by CZE‐C4D without derivatization. Several factors that affect separation, detection and extraction efficiency were investigated. Under the optimum conditions, five haloacetic acids (monochloroacetic acid, dichloroacetic acid, trichloroacetic acid, monobromoacetic acid, and dibromoacetic acid) could be well separated from other components coexisting in water samples within 23 min, exhibiting a linear calibration over two orders of magnitude (r⪖0.9943); the enrichment factors at 430–671 were obtained in a 30 min of extraction, and the limits of detection were in the range of 0.17–0.61 ng/mL. The intraday relative standard deviations for peak areas investigated at 10 ng/mL were between 1.2% and 9.7% for the combined EME‐CZE‐C4D procedure. This approach offers an attractive alternative to the officially proposed method for purified drinking water analysis, which requires derivatization procedure prior to gas chromatography analysis.